Perceptions and Knowledge of Sharia Principles in Islamic Investment: Perspective of Muhammadiyah Community - Bambang Ragil; Ernani Hadiyati; Endang Suswati; Delila Putri Sadayi (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study aims to analyze the perception and knowledge of the Muhammadiyah community - one of the largest religious organizations in Indonesia - towards Sharia principles in investing in Islamic financial products. Using a qualitative approach with Qualitative Data Analysis Software (Q-DAS), data were gathered through in-depth interviews and participatory observations with members of the Muhammadiyah community. The results indicate that the participants have a significant awareness of Sharia principles. They acknowledge the prohibition of usury and the importance of avoiding investments in industries deemed haram according to religious teachings. Participants understood Sharia principles well and used them as guidelines for making investment decisions. However, the study also revealed that the Muhammadiyah community's knowledge of Islamic financial products requires improvement. There is a need for enhanced understanding of the concepts, features, benefits, and risks associated with Islamic financial products. Factors such as access to information, education, previous experience, and religious beliefs influence people's perception and knowledge in this area. The study concludes that while the Muhammadiyah community is highly aware of Sharia principles in investing, a deeper knowledge and broader understanding of Islamic financial products are essential.